ISLAM NUSANTARA: KARAKTERISTIK DAN NILAI - Sarno Hanipudin (AT-THARIQ: Jurnal Studi Islam dan Budaya, 2023)
The purpose of this research is to gain a broad overview of Islam Nusantara, both in terms of its characteristics and the values contained within it. This is a qualitative research study that produces descriptive data in the form of speech, writing, or observed behavior of individuals. The data collection technique involves documentation, accompanied by a detailed analysis. The research results show that there are several educational concepts within Islam Nusantara that can serve as examples for education stakeholders. These concepts and principles include: 1). Concept of Rahmatan Lil’âlamîn: Teaching, instruction, nurturing, and upbringing that embody tolerance, flexibility, moderation, balance, and maintaining harmony. 2). Concept of Akhlak Al-Karimah (Noble Character): Love for the homeland, compassion, love for peace, tolerance, equality, consultation, cooperation, concern, responsibility, appreciation, self-reliance, sincerity, honesty, humility, and patience. 3). Concept of Exemplary Behavior: Intellectual exemplariness, emotional exemplariness, and inspirational exemplariness.